PENGARUH APLIKASI BIOSTIMULAN EKSTRAK DAUN KELOR (Moringa oleifera L) TERHADAP INDEKS TOLERANSI CEKAMAN PADI GOGO PADA BERBAGAI TINGKAT CEKAMAN KEKERINGAN - Ferdiansyah, Awal; Kadir, Muhammad (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Upland rice is susceptible to drought stress in crops, especially on marginal lands. Utilisation of Moringa leaf extract as a biostimulant that is very rich in important compounds is expected to increase plant tolerance to drought stress. This study aims to see the effect of the application of moringa leaf extract as a biostimulant to increase the resistance of upland rice plants to drought stress based on the Stress Tolerance Index (STI) value. The experiment was a 2-factor factorial experiment in a Randomised Completely Block Design pattern of Split Plots Design. The main plot was drought stress consisting of three levels of percentage of Field Capacity (FC), namely 100%, 75%, and 50%. Subplots was the application of Moringa Leaf Extract consisting of four concentration levels: 0% (Control), 5%, 10%, and 15% MLE. The results showed that the application of MLE on upland rice plants at a concentration of 15% gave an average grain yield per hectare of 1445 Kg under moderate stress conditions, and the concentration of MLE gave a Stress Tolerance Index (STI) value of 1.59 under moderate stress and 1.16 under severe stress and both were in the Tolerant category